Managing Islamic Education to Overcome Juvenile Delinquency - M. Rapi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Reconstructing patterns of Islamic education to be basic values of religion provides the scope of Islamic education development. Education is an effort to preserve, transfer and transform cultural good values in all its aspects to the younger generation. Patterns of Islamic education in tackling juvenile delinquency including efforts to improve Muslim education strategies concerning the issue of how the implementation of the educational goals of the educational process by looking at the situation and condition, and also how to keep the process there are no disturbances, internally and externally, regarding institutional or social environments. The application of preventive methods (prevention), curative (treatment) and rehabilitative (quarantine) are pivotal for an educator or school organizers, to coach young people in schools can be focused well; therefore, at least it is to reduce misbehavior frequency among adolescents.